Compaction of chopped material in a mini silo. (August 2020) - Lisowski, Aleksander; Wójcik, Joanna; Klonowski, Jacek; Sypuła, Michał; Chlebowski, Jarosław; Kostyra, Krzysztof; Nowakowski, Tomasz; Strużyk, Adam; Świętochowski, Adam; Dąbrowska, Magdalena; Mieszkalski, Leszek; Piątek, Michał
Abstract: The aim of the study was to explain the effect of pressure and compaction time, number of layers and compaction cycles of biomass from six energy plant species intended for silage on the density of mini silos as well as energy consumption and compaction indicators. A mathematical model was developed to predict the silage density against changed process factors. Chopped biomass was compacted in four layers using three cycles at 17–63 kPa pressure and 6–10 s per cycle. The greatest changes in compacted density were achieved in the first cycle of the first layer. At subsequent stages, the recompression curves were steeper, and more stable and higher densities were obtained. For giant knotweed the required silage dry matter density of 225 kg m −3 was achieved for plants at the physiological maturity stage, with a lower moisture content of 23.6%, than that obtained for plants harvested in June. The silage density was greater for deciduous plants (Virginia mallow and Jerusalem artichoke, but not giant knotweed) than that for grasses (miscanthus, Spartina pectinata, and big bluestem); this result was due to the lower moisture and to differences in the structure of the shoots. Silage density describes the model well in terms of pressure, number of layers, compaction time, particle size and dry matter. Highlights: The compaction of chopped biomass from six energy plant species was studied. Four subsequent layers were compacted in three 6–10 s cycles at 17–63 kPa pressure. The first cycle of the first layer persisted longer at higher pressure. The biomass of deciduous plants was compacted better than that of grasses. A silage density model that includes compaction parameters and biomass properties is presented.